Analisis Perbedaan Minat Beli Di Tokopedia.Com Dan Bukalapak.Com (Studi Kasus Konsumen Tokopedia.Com Dan Bukalapak.com Pada Perguruan Tinggi Di Lingkungan Pondok Pesantren Bahrul Ulum) - Chairul Anam (Journal of Economic, Bussines and Accounting (COSTING), 2024)
In this digital era, business has transformed significantly, using the internet as the primary tool. Sites such as Tokopedia.com and Bukalapak.com, which function as online marketplaces, facilitate sellers to reach buyers more efficiently. This study is directed at exploring and comparing the level of shopping interest in Tokopedia.com and Bukalapak.com. The internet's dramatic evolution in Indonesia has profoundly affected various dimensions of life, especially in the business realm. In this case, the role of individuals as active internet users enables free interaction with fellow users. In the context of interest, a critical element of forecasting buyer behavior, it reflects an individual's reaction to a particular product or service. This study utilizes descriptive and comparative methods, relying on primary and supplementary information. The non-probability and accidental sampling techniques were chosen to determine the research subjects. This study's findings show no notable disparity in purchase intention between Tokopedia.com and Bukalapak.com, a result that provokes businesses to sharpen their competitive tactics in the digital market arena. Keyword: Business Online, Buying of Interest, Market Place